Pattern‐based software process modeling for dependability. Issue 9 (26th March 2020) - Zhang, Xuan; Wang, Xu; Yun, Wei; Gao, Chen; Han, Mengting; Liu, Hui
Abstract: Traditional process modeling focuses on modeling activities for functional requirements. For dependability requirements, a knowledge‐based aspect‐oriented software process modeling approach is proposed. First, we extend the pattern and context to the knowledge graph triplet structure to describe dependability‐oriented knowledge patterns. By applying the patterns, dependability requirements can be organized into dependability‐related activities that are integrated into the software process. Then, aspect‐oriented modeling patterns based on Petri nets are introduced to support the integration of these dependability‐related activities and model dependability‐oriented software processes. Finally, the modeling performance and the subjective usability of the patterns are evaluated by 110 students with different degrees. The results indicate that these two indexes are on the positive track. Hence, the patterns may be the backbone of dependability‐oriented software process modeling. Abstract : Key findings A pattern‐based knowledge model is proposed for dependability requirements in a flexible and reusable way. We propose to extend semantic knowledge structure as a general schema to describe dependability‐oriented knowledge patterns. By applying the patterns, dependability requirements can be organized into dependability‐related activities that are integrated into software process. To ease the integration of dependability‐related activities into software processes, aspect‐oriented modeling patterns based on Petri nets are defined to weave aspects of dependability‐related activities into software processes and model dependability‐oriented software processes. A knowledge‐based aspect‐oriented software process modeling is introduced for dependability improvement. It is helpful for the process improvement in an incremental way at build time. Also, it can facilitate software process control and risk reduction. The modeling performance and the subjective usability of the patterns are evaluated. The results indicate that these two indexes are on positive track. Therefore, the patterns may be the backbone of dependability‐oriented software process modeling.